A pilot study to investigate the feasibility of transporting saliva samples at room temperature with MAWI Cell Stabilization buffer. Issue 1 (1st January 2018) - Lim, Yenkai; Punyadeera, Chamindie
Abstract: Saliva is considered as the front-line of non-invasive diagnostics as novel biomarkers continue to emerge for an array of systemic diseases. Biomarker development pipeline relies heavily on pre-analytical process such as saliva collection, handling, transport and storage. The aim of this study was to systematically evaluate the applicability of MAWI Cell Stabilization ( MCS ) buffer to transport and store saliva samples at room temperature for downstream applications. Human and bacterial genomic DNA (gDNA) and total protein in saliva samples with and without  MCS  buffer were quantified for a week at three time-points at room temperature. Based on our findings,   MCS  buffer was able to preserve human gDNA and total protein within the testing time-points. While bacterial gDNA was accurately preserved,   MCS  buffer was unable to halt bacterial growth at room temperature. We have identified a non-alcohol-based, non-lytic buffer that could maintain the integrity of both genomic materials and proteins in saliva samples.  MCS  buffer offers a method to potentially transport and store saliva samples at room temperature, accelerating the translation of salivary assays in remote/rural and resource limited settings.